CLINICAL STUDY TO COMPARE THE EFFICACY OF NASYA KARMA WITH SHIGRU TAILA AND VIDANGADYA TAILA IN VATAJA PRATISHYAYA (ALLERGIC RHINITIS) - Patil, *Vasant; Uppin, Chennamma; Gupta, Sanjay; Hiremath, Veerayya; Rayanagoudar, S.V.; Kendadamath, D.B. (AYUSHDHARA, 2017)
Background: Vataja pratishyaya is one among the Pratishyaya rogas in which there is vitiation of Vata & Kapha doshas. Currently the conventional medicine has no effective treatment for Allergic Rhinitis. In view of the facts, particularly considering the side effects in the existing methods of treatment, there is the need to develop a treatment protocol. According to Acharya Sharangadhara vairechanik Nasya is the line of treatment. Therefore Nasya has been selected as treatment modality for the present study. “Nasa hi siraso dwaram tena taddapya hanthi tana”. Nose is the gate way of head hence it acts as inlet for the Nasya Karma. It destroys the disease of the head. Objectives: To compare the efficacy of Nasya Karma with Shigru Taila & Vidangadya Taila in Vataja pratishyaya. Methods and Materials: Patients of group A were treated with Shigru Taila Nasya for 7 days & patients of group B were treated with Vidangadya Taila Nasya for 7 days. The dose of Nasya is 6 Bindu. Results: The percentage success rate of Group is A 57.5% & Group-B is 56.8%. There is no significant difference among the results of the treatment of Group-A and Group-B by paired proportion test of significance for i.e. p< 0.001. Conclusion: Patients of group A treated with Shigru Taila Nasya Karma have shown better results clinically compared to group B who were treated with Vidangadya Taila. There were no complications observed during the treatment.